A JSON/HTTP communication protocol to support the development of distributed cyber-physical systems - Pereira, Fernando (2018)
Cyber physical systems are often built using networks of components containing physical and computational resources, enabling the design of distributed applications that collect data from remote sensors and manipulate remote actuators, located on local networks or on far away locations. The communication protocol presented in this paper was designed to support the communication between components of distributed applications. In addition, it includes remote debug and monitoring capabilities, to support the detection and resolution of errors and design mistakes on nodes running on remote locations. Employing the JSON/HTTP standards, the proposed protocol is Web browser friendly, suitable for the creation of Web based applications and user interfaces, but it may be employed on most programming environments that offer libraries to support those standards. As it is based on HTTP, it can easily traverse most firewall configurations and used through proxies. Development of the proposed protocol started on the IOPTTools framework, but the current version was implemented as part of the IOPT-Flow framework, aiming the development of distributed CPS applications based on graphical formalism combining Petri nets and dataflows. Both tool frameworks are available at http://gres.uninova.pt.